2022
DOI: 10.1177/1759720x221114105
|View full text |Cite
|
Sign up to set email alerts
|

Plasma calprotectin as a biomarker of ultrasound synovitis in rheumatoid arthritis patients receiving IL-6 antagonists or JAK inhibitors

Abstract: Objectives: To analyse the accuracy of plasma calprotectin in patients with rheumatoid arthritis (RA) receiving monoclonal antibodies against IL-6 receptors (anti-rIL-6) or JAK inhibitors (JAKis) in detecting ultrasound (US) synovitis and compare it with acute phase reactants [high-sensitivity C-reactive protein (hs-CRP) and ESR]. Methods: An observational cross-sectional study of RA patients receiving anti-rIL-6 (tocilizumab or sarilumab) or JAKi, (baricitinib or tofac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…These results are in line with the existing literature. Previous studies have indicated that this protein re ects a patient's clinical status more accurately than APRs [10][11][12][13], including clinical remission or low disease activity. Furthermore, calprotectin serves as a prognostic biomarker for radiographic progression [50], a marker of therapeutic response to speci c targeted DMARDs (20), and it has proved useful in predicting disease ares in seemingly controlled patients [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in line with the existing literature. Previous studies have indicated that this protein re ects a patient's clinical status more accurately than APRs [10][11][12][13], including clinical remission or low disease activity. Furthermore, calprotectin serves as a prognostic biomarker for radiographic progression [50], a marker of therapeutic response to speci c targeted DMARDs (20), and it has proved useful in predicting disease ares in seemingly controlled patients [51].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when secreted into the synovium, calprotectin subsequently enters peripheral blood circulation. Levels of calprotectin in serum or plasma have been found to correlate closely with in ammatory disease activity in RA patients and therefore provide a more accurate re ection of the patient's clinical status than APRs [10][11][12][13].…”
mentioning
confidence: 99%
“…To reduce variation in calprotectin determinations, the whole procedure was performed in a Triturus Autoanalyzer; the coefficients of variation were 5% within and 13% between assays. This technique had already been used by our group for previous studies[ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…To ensure strict criteria for defining US synovitis, only patients with SH grade ≥ 2 plus PD signal ≥ 1 were considered to have active synovitis [ 37 ]. This US assessment method had been previously employed in prior studies conducted by our group [ 11 ]. Clinically symptomatic joints were also evaluated to assess whether US synovitis was present.…”
Section: Methodsmentioning
confidence: 99%
“…Increased calprotectin expression has also been found in patients with rheumatic diseases [20]. In rheumatoid arthritis (RA) patients, serum and plasma calprotectin levels are sensitive markers of inflammation [21,22] and have been associated with radiographic damage [23]. In addition, calprotectin can be a biomarker of clinical responses to antirheumatic drugs [24] and a predictive factor for disease relapse [25].…”
Section: Introductionmentioning
confidence: 99%